Nanoarchitectonics of low process parameter synthesized porous carbon on enhanced performance with synergistic interaction of redox-active electrolyte for supercapacitor application - Samantray, R.; Manickavasakam, K.; Vivekanand, .; Pradhan, B.; Kandasamy, M.; Mishra, S. C.; Izan Izwan, Misnon; Jose, Rajan (Elsevier, 2024)
To develop materials of lower embodied energy and materials footprint for energy storage industry, the present work reports synthesis of porous carbon from a waste wetland weed (wild sugarcane) using low process parametric conditions (temperature and impregnation ratio) and their electrochemical capacitive (synonymously known as supercapacitors) charge storage performance in aqueous and redox active electrolytes. The phase, surface chemistry, physical surface, and morphology of the porous carbon thus developed are studied in detail using X-ray diffraction, gas adsorption measurements, Fourier-transform infrared spectroscopy, X-ray photoelectron spectroscopy, scanning and transmission electron microscopy techniques. Porous carbon synthesized at 500 °C, with the activator ZnCl2, resulted in a combination of micro and meso pores and a specific surface area ∼1294 m2 g−1. The optimized electrodes show outstanding energy storage performance, viz. specific capacitance of ∼414 F g−1 (three-electrode system) and ∼197 F g−1 (two-electrode system) at 1 A g−1 current density in aqueous 1 M H2SO4 electrolyte. The porous activated carbon showed high performance in terms of electrochemical stability of 96 % in half cell configuration for 10,000 cycles, while the symmetric device showed 80 % cyclic stability for 5000 cycles in full cell configuration. Addition of redox active 0.01 M hydroquinone in the 1 M H2SO4 significantly improved the storage capacity to 540 C g−1 at current density of 3 A g−1 in two-electrode configuration and maintained 72 % of capacity for 5000 cycles. The redox-active symmetric supercapacitors show an energy density ∼26.9 W h kg−1 and power density ∼5527 W kg−1 and other related electrochemical properties.